The Effect of Roleplay to Increase Empathy Toward Students with Disruptive Classroom Behavior - Dewi, Yoan Tricylia; Pratisti, Wiwien Dinar; Prasetyaningrum, Juliani (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2019)
Purpose: This study aims to find effectiveness of role playing toward the students with disruptive classroom behavior. Empathy being important part for adolescents development to ensure that adolescents avoid harmful behaviors to others and capable to adapt in the environment. Lack of empathy in adolescents appears to be a neglectful attitude towards the social environment and often disrupts the social environment. Although empathy is considered as an emotional state, empathy often has a cognitive component in the form of the ability to see psychological states in others, or also called by taking the perspective of others so that empathy is considered important to reduce disruptive behavior in class. Role playing can help someone form a deeper understanding of certain situations so that they are able to see from another’s point of view. Method: The subjects in this study were 8th grade students of SMP Swasta Kartasura who had average and low empathy categories as well as had high disruptive behavior. There are 32 subjects in this study who were divided into 2 groups by matching sampling that known as the control group and the experimental group. This study used an empathy scale with the pretest-posttest control group design experimental design to collected the data.Scale validity test used content validity test, with the help of expert judgement which was carried out by six experts. Based on the results of calculations using the Aiken formula on 58 items of empathy scale, it could be obtained four items with a value below 0.79, so that there were 54 valid items. Meanwhile, the reliability of the empathy scale was measured using Alpha Cronbach’s reliability. The results of the empathy scale trial showed that the Alpha reliability value obtained was 0.86, so it was appropriate to be used in the measurement of empathy for junior high school students. The empathy scale, which totaled 54 items, changed after the trial, in which one item eliminated, and 53 items were appropriate for use in the study scale.Results: Hypothesis testing in this study uses the technique of Independent Sample T-Test with z = -4,138 and sig. (2-tailed) = 0,000 where p <0.01, which means that there is a significant difference in the level of empathy between groups that got the role playing training compared to groups that are not got the role playing training. Thus, training plays an effective role in increasing empathy in students with disruptive behavior in class. Empathy increase gradually occurs in two subjects, while other subjects experience an increase directly from average to high. There was also one subject who had no change in empathy scores at follow-up data.